2023
DOI: 10.1161/strokeaha.123.042794
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Recanalization Attempts and Functional Outcome After Thrombectomy for Large Ischemic Stroke

Abstract: BACKGROUND: Recently, 3 randomized controlled trials provided high-level evidence that patients with large ischemic stroke achieved better functional outcomes after endovascular therapy than with medical care alone. We aimed to investigate whether the clinical benefit of endovascular therapy is associated with the number of recanalization attempts in extensive baseline infarction. METHODS: This retrospective multicenter study enrolled patients from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…While the benefit of first-pass effect is well described in patients who do not have large core to begin with, it would be prudent to understand its role in large core thrombectomy population. The study by Winkelmierer et al 20 in the current issue offers valuable insight on this important question. In this retrospective study of the German Stroke Registry data set, the authors examined the role of large core thrombectomy in patients with low Alberta Stroke Program Early Computed Tomography Score (3-5).…”
Section: Mehta and Gonzalezmentioning
confidence: 91%
“…While the benefit of first-pass effect is well described in patients who do not have large core to begin with, it would be prudent to understand its role in large core thrombectomy population. The study by Winkelmierer et al 20 in the current issue offers valuable insight on this important question. In this retrospective study of the German Stroke Registry data set, the authors examined the role of large core thrombectomy in patients with low Alberta Stroke Program Early Computed Tomography Score (3-5).…”
Section: Mehta and Gonzalezmentioning
confidence: 91%
“…The authors Winkelmeier et al . [ 16 ] investigated the role of thrombectomy in patients with ASPECTS 3–5 and among the 348 patients included, 83.3% achieved mTICI 2b/3 recanalization and 36.2% experienced favorable outcomes, aligning with the randomized trial data.…”
Section: Discussionmentioning
confidence: 84%
“…Our study demonstrated that patients with unsuccessful recanalization and general anesthesia were more likely to develop post-EVT infection, which was not entirely consistent with the results of previous studies. 25,[36][37][38] Successful recanalization after endovascular treatment has been reported to be closely related to clinical prognosis. 39,40 Failure of recanalization leads to poor cerebral blood flow revascularization, which may lead to more severe neurological deficits and an altered state of consciousness, thereby contributing to the development of post-EVT infection.…”
Section: Discussionmentioning
confidence: 99%